Revision of Taiwanaenidea Kimoto, 1984 (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng; Beenen, Ron (Zootaxa, 2015)
The genus Taiwanaenidea Kimoto, 1984 is a little-known galerucine genus known only with original description, which lacks illustrations. A number of specimens belonging to this genus are now available for study with effective collection made by Taiwan Chrysomelid Research Team. Two new species, T. cheni Lee and Beenen sp. nov. and T. jungchangi Lee and Beenen sp. nov. are here described. The other two known species, T. collaris Kimoto, 1984 and T. strigosa Kimoto, 1984 are reviewed and illustrations of diagnostic characters are presented. A key to all species of this genus is provided.